Process optimization and influence of processing conditions on physical, thermal and textural characteristics of Nigerian pasta produced from acha flour and defatted Moringa oleifera powder - Akeem Olayemi Raji; Isiaka Mubarak Olaitan; Maxwell Yemmy Mitchel Omeiza; Mayowa Saheed Sanusi (Food Physics)
The consumption of Nigerian lesser known crops has been advocated by many researchers. Replacement of wheat flour with acha (Digitaria exilis) and de-fatted Moringa oleifera cake in pasta production at a laboratory scale was investigated to determine their suitability in functional pasta production. Optimization process of pasta production from acha flour (AF) and defatted Moringa oleifera powder (DMP) carried out using standard method, with the objectives of determining optimum processing condition by applying hybrid of Taguchi Orthogonal Array Design and Response Surface Methodology of Design Expert version 6.0. The independent variables were barrel temperature (90 – 110 oC), barrel speed (240 – 360 rpm) and moisture content (30–40%). The responses ranged as follows: hardness (18.96 – 27.83 N), springiness (0.41 – 0.71), adhesiveness (0.09 – 0.59 N/m2), cohesiveness (0.35 – 0.64), chewiness (3.85–11.89 N/m2), gumminess (9.23 – 17.63 N/m2), colour characteristics (L* [0.07 – 2.20], a* [0.32 – 1.07] and b* [0.21 – 2.11]), cooking time (4.00 – 6.00 min), cooking loss (5.66 – 8.05 g/100 g), water uptake (95.27–137.27%), elongation ratio (0.82 – 1.08), specific heat capacity (Cp) (177.31 – 196.45 kJ/kg/K), thermal conductivity (27.31–29.64 W/m/K) and thermal diffusivity (8.17 – 8.81 ×10−6 m2/s). The variation in processing conditions significantly (P < 0.05) influenced all the responses. However, the principal component analysis (PCA) of the physical, thermal and instrumental textural characteristics of pastas showed positive correlations except for adhesiveness and overall acceptability. Conclusively, dough moisture content of 39.85%, barrel speed of 240 rpm and barrel temperature of 110°C gave the optimal extrusion process condition for the production of high-quality pasta.